A multicenter analysis of implantable monitoring device-based diagnosis of supraventricular arrhythmia post patent foramen ovale closure: the OCCL-ILR study - Lochy, Stijn; Del Monte, Alvise; Galloo, Xavier; Motoc, Andreea; Plein, Daniele; Hermans, Kurt; Gorré, Frauke; Colas-Florial, Julie; Rosseel, Liesbeth; Muyldermans, Philip; Pauwelyn, Maarten; Palmers, Pieter-Jan; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRecent data suggest that the true incidence of atrial fibrillation (AF) after patent foramen ovale (PFO) closure has probably been underestimated, and may differ according to the type of closing device used.ObjectivesOn the basis of continuous rhythm monitoring with an implantable device, this study aims to assess the incidence of  supraventricular arrhythmia following PFO closure with the Occlutech PFO device.MethodsThis is a multicentric analysis of consecutive PFO closure patients treated with an Occlutech device between 01/01/2019 and 20/03/2024, with an implantable loop recorder (IRL) (or a pacemaker or implantable cardioverter defibrillator) implanted for at least 3 months preceding the procedure, and with available follow-up for at least 1month post procedure. Primary endpoint was the incidence of patients with new onset supraventricular arrhythmia (AF, atrial flutter or any supraventricular tachycardia) lasting >30 s, post PFO closure.ResultsA total of 59 patients met the inclusion criteria. Patients were monitored (95% with ILR) during 284 days (IQR 241.5–374) before, and for 422 days (IQR 237–776) post PFO closure. Supraventricular arrhythmia post PFO closure was reported in 18 patients (31%), with median time-interval until arrhythmia occurrence of 16.5 days (IQR 13–21). A total of 88 supraventricular arrhythmia events (96.6% AF) were documented during follow-up. In 94.4% of patients with supraventricular arrhythmia, new-onset arrhythmia occurred in the first 45 days after PFO closure. Six patients (33.3%) with supraventricular arrhythmia post PFO closure, presented AF episodes beyond 60 days after PFO closure.ConclusionsIn this multicenter retrospective analysis of patients undergoing percutaneous PFO closure with the Occlutech PFO device, implantable continuous rhythm monitoring devices were able to diagnose new-onset supraventricular arrhythmia (97% AF) after PFO closure in 31% of patients. While 94% of new-onset supraventricular arrhythmia events occurred in the first 45 days post-procedure, one-third of patients with arrhythmia post PFO closure presented AF episodes beyond 60 days post procedure.